THE USE OF AUTHENTIC MATERIALS IN TEACHING ENGLISH TRANSLATION - Natsir, Ratu Yulianti; Atmowardoyo, Haryanto; Mahmud, Murni (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research aimed to know the improvement of the students’ translation skills through Authentic Materials at the fifth semester of English Department. Pre-experimental design was used in this research with the population was consist of 180 students and applied purposive sampling technique and the chosen 30 students were taken as samples. It employed of six meetings (one meeting for pre-test, four meetings for treatment, and one meeting for post-test). The instrument was in the form of translation test of English News into Indonesia The result of this research showed that the authentic materials in learning translation had good impact to students’ translation competence. The use of authentic materials was effective to improve and to provide feedback to the students’ translation ability for the fifth semester of UNISMUH Makassar. The test results show that the test value of t-test is greater 7.774 with sig of 0.000. It shows that the use of authentic materials in the form of news text significantly improve students’ translation achievement and suggest that using authentic materials in learning translation.